2005
DOI: 10.1090/conm/369/06807
|View full text |Cite
|
Sign up to set email alerts
|

On the uniqueness of ℂ*-actions on affine surfaces

Abstract: It is an open question whether every normal affine surface V over C admits an effective action of a maximal torus T = C * n (n ≤ 2) such that any other effective C * -action is conjugate to a subtorus of T in Aut(V ). We prove that this holds indeed in the following cases: (a) the Makar-Limanov invariant ML(V ) = C is nontrivial, (b) V is a toric surface, (c) V = P 1 × P 1 \∆, where ∆ is the diagonal, and (d) V = P 2 \Q, where Q is a nonsingular quadric. In case (a) this generalizes a result of Bertin for smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 2 publications
2
55
0
Order By: Relevance
“…For instance, we show in Section 6.3 how to classify C + -actions or, equivalently, A 1 -fibrations on Gizatullin surfaces; see Theorem 6.3.18. In Section 6.4 we strengthen our previous uniqueness result [FlZa3] for A 1 -fibrations on (singular, in general) Gizatullin surfaces.…”
Section: 02supporting
confidence: 79%
See 3 more Smart Citations
“…For instance, we show in Section 6.3 how to classify C + -actions or, equivalently, A 1 -fibrations on Gizatullin surfaces; see Theorem 6.3.18. In Section 6.4 we strengthen our previous uniqueness result [FlZa3] for A 1 -fibrations on (singular, in general) Gizatullin surfaces.…”
Section: 02supporting
confidence: 79%
“…In [FlZa3,FKZ3] we have shown that a C * -action on a smooth affine surface V is unique up to equivalence unless V belongs to one of the classes (1)-(3) in Theorem 1.0.1 (see also 3.5.2 and 3.5.3 below). A similar uniqueness theorem holds for A 1 -fibrations V → A 1 ; see [FKZ3,5.13] and Proposition 6.4.1 in Section 6.4. Thus Theorem 1.0.1 is a consequence of the following result.…”
Section: 02mentioning
confidence: 98%
See 2 more Smart Citations
“…We get the following corollary as an immediate consequence, see also [9]. For the classification of Z d -homogeneous fibration with C * fibers we first state the non-equivariant version used in [6], see also [23].…”
Section: See That a Is A D-th Root Of Unity And Thus (3) Implies (1)mentioning
confidence: 93%